Assistance in the use of maternal and child health (MCH) book on the behavior of pregnant women in health services - Prihatin, Nova Sumaini; Elizar, Elizar; Rosyta, Rosyta; Jasmiati, Jasmiati; Nurmila, Nurmila; Putri, Hendrika Wijaya Katrini; Irnawati, Irnawati (Institute of Computer Science (IOCS), 2025)
The Maternal and Child Health (MCH) Book includes health records of both mother and child from pregnancy through the child’s fifth year, and functions as a communication tool among healthcare providers, pregnant women, and their families. Strengthening the use of the MCH Book among mothers aims to enhance their understanding of its function in health monitoring and as a source of health information. This study aims to examine the effectiveness of facilitated use of the Maternal and Child Health (MCH) Book on pregnant women's health service-seeking behavior during pregnancy within the working area of Banda Sakti Health Center. This study utilized a pre-experimental design with a one-group pre-test and post-test model. The research was conducted within the working area of the Banda Sakti Public Health Center. A total of 52 pregnant women were selected as participants. Data were collected using a structured questionnaire, and statistical analysis was performed using the Wilcoxon signed-rank test. The findings indicated that guided use of the Maternal and Child Health (MCH) Book significantly improved pregnant women's knowledge and health-seeking behaviors during pregnancy.